2010
DOI: 10.1590/s1726-46342010000400006
|View full text |Cite
|
Sign up to set email alerts
|

Efecto vasodilatador mediado por óxido nítrico del extracto hidroalcohólico de Zea mays L. (maíz morado) en anillos aórticos de rata

Abstract: Objetivo. Evaluar la respuesta vasodilatadora e inhibidora de la vasoconstricción del extracto hidroalcohólico de Zea mays L. (maíz morado) y determinar si esta respuesta es mediada por óxido nítrico (NO). Materiales y métodos. Se obtuvo un extracto de las corontas de maíz morado maceradas durante ocho días en etanol al 70%, y posterior concentración del producto. Se trabajó con anillos aórticos de rata en cámara de órganos aislados, bañada con solución Krebs-Hensleit (K-H) y se registró la actividad vasomotor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
1
0
2
Order By: Relevance
“… 25 It has been shown that the physiological responses induced by purple corn extracts are mainly mediated by nitrergic activity. 26 The exact mechanism through which the purple corn aqueous crude extract is exerting its aphrodisiac actions was not investigated in the present study, but it could proposed that its pro-sexual activity, centered on the sexual performance seen in copulating rats and those obtained in an increased ejaculation potency and capacity seen in the fictive ejaculation model, are due to its nitrergic activity. In line with notion, it has been demonstrated that nitric oxide participates in male sexual behavior of rats by increasing the indexes of sexual performance 27 and by promoting penile erection in intact male rats.…”
Section: Discussionmentioning
confidence: 77%
“… 25 It has been shown that the physiological responses induced by purple corn extracts are mainly mediated by nitrergic activity. 26 The exact mechanism through which the purple corn aqueous crude extract is exerting its aphrodisiac actions was not investigated in the present study, but it could proposed that its pro-sexual activity, centered on the sexual performance seen in copulating rats and those obtained in an increased ejaculation potency and capacity seen in the fictive ejaculation model, are due to its nitrergic activity. In line with notion, it has been demonstrated that nitric oxide participates in male sexual behavior of rats by increasing the indexes of sexual performance 27 and by promoting penile erection in intact male rats.…”
Section: Discussionmentioning
confidence: 77%
“…Estos fitoquímicos, presentes en el maíz morado, tienen efectos benéficos, tales como su capacidad antioxidante o de neutralización de radicales libres y actúan como antimutagénicos [19,20,21]. En el organismo humano, los factores vitamínicos del maíz morado son utilizados como protectores capilares y venosos [22,23] que previenen problemas de ateroesclerosis [24]. Además, ayudan a prevenir enfermedades cardiovasculares, ya que estimulan la circulación de la sangre y protegen los vasos sanguíneos de un posible deterioro oxidativo (ayudan a prevenir el envejecimiento prematuro).…”
Section: Introductionunclassified
“…Estos fitoquímicos, presentes en el maíz morado, tienen efectos benéficos, tales como su capacidad antioxidante o de neutralización de radicales libres y actúan como antimutagénicos [19,20,21]. En el organismo humano, los factores vitamínicos del maíz morado son utilizados como protectores capilares y venosos [22,23] que previenen problemas de ateroesclerosis [24]. Además, ayudan a prevenir enfermedades cardiovasculares, ya que estimulan la circulación de la sangre y protegen los vasos sanguíneos de un posible deterioro oxidativo (ayudan a prevenir el envejecimiento prematuro).…”
Section: Introductionunclassified